KONTRIBUSI KESUKSESAN RANTAU TERHADAP PENINGKATAN EKONOMI MASYARAKAT DI DAERAH ASAL (STUDI USAHA FOTOKOPI MASYARAKAT ATAR) - Arianti, Farida (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2017)
This study investigated the contribution of the success of local migrants (perantau) from Atar toward the economic development of the community in the region of origin, and the factors contributing to the success . This study was a quantitative research that sought the extent of the contribution of the success of perantau to the economic development of communities in the area of origin. The data were collected by using questionnaire and analyzed by using linear regressional analysis. The findings showd that the influence of solidarity on economic improvement can be seen as follow: Y = 23.326 + 0.014. X. This showed that each one unit solidarity increased the economy of 0.014. Factors contributing to the impact of the success were the desire to develop Atar community in the business of photocopying. In addition, seeking independent work and not becoming employee forever.